𝒌𝒕𝒉 FIBONACCI PRIME LABELING OF SNAKE GRAPHS - Anna S. Varghese; Gerard Rozario Joseph; Lawrence Rozario Raj P. (Journal of Mechanics of Continua and Mathematical Sciences)
kth Fibonacci Prime Labeling is defined as labeling the vertices of a graph with distinct Fibonacci numbers starting since the kth Fibonacci term sustaining the condition that the 𝑔𝑐𝑑(𝑓(𝑢), 𝑓(𝑣)) = 1, where 𝑓(𝑢) and 𝑓(𝑣) are labels of any adjacent vertices u and v. Graphs formed by consecutively connecting identical base graphs, linearly or in alternating pattern, is called Snake graph. In this paper, we show that some snake graphs admit kth Fibonacci prime labeling.